Influence of Different Malocclusion Traits on Overall Orthodontic Treatment Duration: A Retrospective Cohort Study - Farhan Ali, Adil Gulzar, Maha Butt, Saadia Nazir, Maham Arshad, Muhammad Talha (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The specific traits of malocclusion at the outset of comprehensive orthodontics have a significant impact on the overall treatment time for fixed appliances. Material and Methods: A retrospective cohort study of 452 patients who received comprehensive orthodontic treatment with fixed appliances between July 2020 and June 2023 in the university orthodontic clinic was performed. The following malocclusion characteristics were systematically recorded as baseline measurements: severity of crowding, sagittal relationship, vertical discrepancies (overbite), transverse discrepancies (crossbite), rotations (>20°), and impacted teeth. One-way ANOVA and multivariable linear regression were used to analyze data after the control of confounding variables including age, sex and extraction status. Results: The average overall treatment period was 24.3 ± 6.2 months. The factors of severe crowding (>6 mm), Class II Division 1 malocclusion, deep overbite, and impacted canines were all found to be statistically significant factors that increased the length of treatment (p < 0.05). Conclusion: There are certain malocclusion characteristics such as severe crowding, Class II Division 1 sagittal discrepancy and impaction of canines that significantly increase overall orthodontic treatment time. Clinicians can make more accurate treatment time estimates and design biomechanical strategies to maximize treatment efficiency when they recognize these at the diagnostic stage. Keywords: Malocclusion, Orthodontic treatment duration, Crowding, Overjet, Retrospective study, Fixed appliances, Tooth movement.